The concepts of surveillance and sousveillance: a critical analysis - Thomsen, Frej Klem (Social Science Information)
The concept of surveillance has recently been complemented by the concept of sousveillance. Neither term, however, has been rigorously defined, and it is particularly unclear how to understand and delimit sousveillance. This article sketches a generic definition of surveillance and proceeds to explore various ways in which we might define sousveillance, including power differentials, surreptitiousness, control, reciprocity, and moral valence. It argues that for each of these ways of defining it, sousveillance either fails to be distinct from surveillance or to provide a generally useful concept. As such, the article concludes that academics should avoid the neologism, and simply clarify what sense of surveillance is at stake when necessary. - Reproduced.